Te Deum Laudamus – Grosser Gott, wir loben dich. A discussion of translations in Afrikaans - Kloppers, Elsabé (HTS teologiese studies, 2020)
Te Deum Laudamus – Grosser Gott, wir loben dich. A discussion of translations in Afrikaans. The German hymn ‘Grosser Gott, wir loben dich’, written by the Catholic priest, Ignaz Franz (1719–1790), is based on the ‘Te Deum’, one of the oldest hymns in the Christian tradition. The ‘Te Deum’ and the original German text of ‘Großer Gott’ are discussed and a short overview of the reception of the text is given. It is followed by a discussion of translations into Afrikaans: a text in a Lutheran hymnal, the two versions included in the second official hymnal of the Dutch Reformed Churches in South Africa (1978), and another version, also included in the current (third) official hymnal, Liedboek van die Kerk (2001). Theological and hymnological aspects, as well as connections and similarities with the ‘Te Deum’ and the original text in German are investigated.Contribution: The background and reception history of the hymn Grosser Gott, wir loben dich are given, and various translations into Afrikaans are discussed with regard to differences and similarities to the original text. It is shown that changes to texts could contribute to hymns being used to promote strange issues.